EFEK PEMBERIAN PUPUK KASCING DAN UREA TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) - Novita, Rika Yeli; Khoiri, M. Amrul; ', Sampoerno (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Organic fertilizers can be used for a cacao nursery is vermicompost, whereas inorganic fertilizer that can be used are urea. The purpose of this study was to determine the effect of vermicompost fertilizer and urea as well as getting the best combination treatment for the growth of cocoa seedlings. This research used experimental method using a completely randomized design (CRD) with 2 factors and 3 replications. The first factor is the dose of vermicompost fertilizer (K) which consists of 4 levels and the second factor is the dose of urea (U), which consists of 4 levels. The parameters measured were seedlings height (cm), number of leaves (leaf), girth (cm), leaf area (cm2), ratio feature roots and dry weight (g). The data analysis results were significant statistical test followed by Duncan's test New Multiple Range Test (DNMRT) at the 5% level. The conclusion of this analysis is that combination treatment of vermicompost fertilizer at a dose 75 g/polybag and urea 0.750 g/polybag affect leaf area and ratio feature roots. Vermicompost fertilizer factor at a dose of 75 g/polybag on cocoa seedlings affect seedlings height, girth, leaf area, ratio feature roots and dry weight, but had no effect on the number of leaves. Urea fertilizer factor at a dose of 0.750 g/polybag on cocoa seedlings affect seedlings height, leaf area and ratio feature roots, but did not affect the number of leaves, girth and dry weight. Keywords: cocoa, vermicompost, urea, combination treatment